2007
DOI: 10.1088/0031-9155/52/13/005
|View full text |Cite
|
Sign up to set email alerts
|

Damage to plasmid DNA induced by low energy carbon ions

Abstract: The damage induced in supercoiled plasmid DNA molecules by 1-6 keV carbon ions has been investigated as a function of ion exposure, energy and charge state. The production of short linear fragments through multiple double strand breaks has been demonstrated and exponential exposure responses for each of the topoisomers have been found. The cross section for the loss of supercoiling was calculated to be (2.2 +/- 0.5) x 10(-14) cm(2) for 2 keV C(+) ions. For singly charged carbon ions, increased damage was obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
1
25
1
Order By: Relevance
“…[10,11] Since DNA carries the genetic information, most of the studies have been focused on its constituents. Films of plasmid DNA have been irradiated by low-energy electrons, [12] keV singly and multiply charged ions, [13,14] and more recently by swift ions. [15] At the molecular level, the fragmentation of nucleobases by low-energy electrons, [16,17] low-energy ions [18,19] and 100 keV protons [20,21] has been studied in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Since DNA carries the genetic information, most of the studies have been focused on its constituents. Films of plasmid DNA have been irradiated by low-energy electrons, [12] keV singly and multiply charged ions, [13,14] and more recently by swift ions. [15] At the molecular level, the fragmentation of nucleobases by low-energy electrons, [16,17] low-energy ions [18,19] and 100 keV protons [20,21] has been studied in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…A good way to study this issue is to use low-energy and low-fluence ions to directly bombard naked DNA in vitro to simulate the final-step interaction between the ions and DNA. There have been some investigations done on various low-energy radiations including low-energy ion bombardment of DNA [5][6][7][8][9][10]. The results showed that low-energy ions could produce plasmid DNA strand breaks.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary, singly ionised species can be formed through fragmentation events while multiply charged secondary ions are likely to be produced through Auger de-excitation following core ionisation by the primary particle [4]. Recently [5] we have investigated the interaction of singly and doubly charged, low energy, carbon ions with solid phase plasmid DNA and observed single, double and multiple double strand breaks. It was also observed that, for the same kinetic energy (2 keV), doubly charged ions induced more strand breaks than singly charged ions, indicating that the release of the potential energy of the ion was also important in the interaction.…”
Section: Introductionmentioning
confidence: 99%